TANTANGAN EKONOMI DAN KELEMBAGAAN PETANI KECIL SWADAYA SAWIT DI INDONESIA - Luci Paonganan (Agros Journal of Agriculture Science, 2023)
Oil palm smallholders (farmers) are the second largest group of palm oil producers in Indonesia. It consists of plasma smallholders namely farmers whose plantation activities are supported or in collaboration with oil palm companies and independent smallholders whose plantation activities are carried out independently. This study aims to determine the economic challenges faced by oil palm independent smallholders as well as institutional challenges and solutions expected by them. This research is an exploratory research with survey method and analyzed by descriptive statistics. Primary data collection was carried out by using a questionnaire method. Research respondents consisted of 109 oil palm independent smallholders in 14 provinces in Indonesia. The aspects surveyed included a general description of the independent smallholder, aspects of economic challenges, institutional aspects and the solutions expected by farmers. The results showed that the main economic challenge faced by independent smallholder of oil palm is the fluctuating and low selling price of fresh fruit bunches (FFB). Most of the farmers do not join farmer organizations because of the unavailability of farmer organizations. The institutional model preference is a farmer-managed cooperative. Solutions expected by farmers include protection of the FFB sale price, availability of farmer institutions, access to palm oil mills, infrastructure improvements and training on good agricultural practices.